Pengaruh Kompetensi, Independensi, Profesionalisme, Tekanan Anggaran Waktu, Dan Fee Audit Terhadap Kualitas Audit (Studi Empiris KAP Jateng dan DIY) - Suryananda, Oza Tiara, Drs. Wahyono, MA, Ak (2017)
This research aims to analyze the effect of auditor competence, independence, professionalism, time and budget pressures fee audit of the quality of the audit on public accountant in Central Java and Yogyakarta These studies use quantitative methods using primary data obtained from the questionnaire. The population of this research is the auditor of the level of partner, Manager, senior, and junior who worked on the hood of Central Java and Yogyakarta, 2016 to obtain permission from the Minister of finance, not in the circumstances a furlough, and other causes. Sample assignment method used is the purposive sampling. The sample in this research as much as 45 respondents. The results showed that significant influential variable competence against the quality of the audit. The independence of the influential variables are significant to the quality of audits. Variable has no effect significant professionalism to quality audits. Variable Time influential Budget Pressures significantly to the quality of the audit. The variable Fee Audits do not affect significantly the quality audit.